Football and economy before and after communism in Romania - Sorin D. BUHAŞ; Grigore Vasile HERMAN; Paul F. DRAGOŞ; Lucian STANCE (Editura Universităţii din Oradea, 2017)
The present study aims at identifying the relations between football and the Romanian economy before and after the communist period (1986 - 2005). This study was based on bibliographic analyzes and analytical interpretations, in time and space, of the information regarding the number of teams in League III and of the relationships they develop with the economic environment. The results reflect the profound mutations that economy and sports has experienced during the passage of the Romanian society from a communist society to a capitalist one. The indissoluble link between football and the economic environment is evident especially for teams in League III.